An Iron-Regulated Alkyl Hydroperoxide Reductase (AhpC) Confers Aerotolerance and Oxidative Stress Resistance to the Microaerophilic Pathogen Campylobacter jejuni - Baillon, Marie-Louise A. (American Society for Microbiology, 1999)
Microaerophiles like Campylobacter jejuni must resist oxidative stresses during transmission or infection. Growth of C. jejuni 81116 under iron limitation greatly increased the expression of two polypeptides of 26 and 55 kDa. The identification of these proteins by N-terminal amino acid sequencing showed both to be involved in the defense against oxidative stress. The 55-kDa polypeptide was identical to C. jejuni catalase (KatA), whereas the N terminus of the 26-kDa polypeptide was homologous to a 26-kDa Helicobacter pylori protein. The gene encoding the C. jejuni 26-kDa protein was cloned, and the encoded protein showed significant homology to the small subunit of alkyl hydroperoxide reductase (AhpC). The upstream region of ahpC encoded a divergent ferredoxin (fdxA) homolog, whereas downstream sequences contained flhB and motB homologs, which are involved in flagellar motility. There was no evidence for an adjacent homolog of ahpF, encoding the large subunit of alkyl hydroperoxide reductase. Reporter gene studies showed that iron regulation of ahpC and katA is achieved at the transcriptional level. Insertional mutagenesis of the ahpC gene resulted in an increased sensitivity to oxidative stresses caused by cumene hydroperoxide and exposure to atmospheric oxygen, while resistance to hydrogen peroxide was not affected. The C. jejuni AhpC protein is an important determinant of the ability of this microaerophilic pathogen to survive oxidative and aerobic stress.